Food Security and Food Safety for the Twenty-first Century: Proceedings of APSAFE2013 - Hongladarom, Soraj (Springer, 2015)
This book is a collection of selected papers that were presented at the First International Conference of the Asia-Pacific Society for Agricultural and Food Ethics (APSAFE 2013), which was held at Chulalongkorn University from November 28 – 30, 2013. The papers are interdisciplinary, containing insights into food security and food ethics from a variety of perspectives, including, but not limited to, philosophy, sociology, law, sociology, economics, as well as the natural sciences. The theme of the conference was to consider the interplay and balance between food security and food ethics as the world approaches the middle part of the twenty-first century.